2014
DOI: 10.5455/ijlr.20140109084416
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Intensity of Eimeria Infection in Sheep in Western Iran

Abstract: The present study was carried out to survey the prevalence and intensity of coccidia in sheep in western Iran. The prevalence of coccidial infection was monitored in 410 sheep in western Iran between March 2012 to February 2013. Oocysts in faecal samples were detected using a flotation technique, sporulated and identified to species based on morphological features of the sporulated oocysts. The overall prevalence of coccidial infection was 91.5% (375/410

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
2
3
0
2
Order By: Relevance
“…In the present study, some lambs grazed with adults in a communal grazing system, which exposed them to mild infection. In the studies conducted by Maingi and Munyua (1994), Craig et al (2006), andHashemnia et al (2014), nematode and coccidial infections of lambs were reported, which was consistent with the results of the current study. They explained that male sheep were prone to gastrointestinal helminths because of the production of androgen hormones, which seem to suppress the immune response of the male sheep.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, some lambs grazed with adults in a communal grazing system, which exposed them to mild infection. In the studies conducted by Maingi and Munyua (1994), Craig et al (2006), andHashemnia et al (2014), nematode and coccidial infections of lambs were reported, which was consistent with the results of the current study. They explained that male sheep were prone to gastrointestinal helminths because of the production of androgen hormones, which seem to suppress the immune response of the male sheep.…”
Section: Discussionsupporting
confidence: 92%
“…Molecularly the results recorded five different species of Eimeria in sheep that which E. ahsata 33.33% E. weybridgensis 22.22%, E. ovinoidalis 16.66%, E. bovis 16.66% and E. auburnensis 11.11%, where the first three species are a specific for sheep, while the two later a specific for cattle. These results are agreed with the result of Platzer et al (21) who recorded three species included E. ovinoidalis, E. weybridgensis and E. ahsata in Austria, Hashemni et al (22) who recorded E. ahsata in Western Iran and Kara (23) who confirmed E. ovinoidalis in Turkey.…”
Section: Discussionsupporting
confidence: 91%
“…Also, disconformity with the findings from [21] which reported prevalence rate 67.5% of coccidia in sheep in the province of AL-Muthanna but in Garmiyan Province, Kurdistan region recorded a low ratio of coccidiosis in sheep about 31.30% [22] all these reports recorded in Iraq, as well as in sheep of other countries. In Iran, the rate of Eimeria in sheep was 240 positive, the total rate of coccidiosis in sheep was 19.2% [23] . And in the Colombian Northeastern Mountain [24] which recorded prevalence of Eimeria spp.…”
Section: Discussionmentioning
confidence: 99%